Maladaptive behavioural phenotypes in captive‐reared darters (Etheostoma caeruleum, Storer 1845). (25th March 2015) - Crane, A. L.; Lampe, M. J.; Mathis, A.
Summary The foraging and anti‐predator behaviour of captive‐reared rainbow darters (Etheostoma caeruleum) was compared to their wild‐caught counterparts. Wild‐caught darters responded with appropriate anti‐predator behaviour (reduced foraging activity) when exposed to alarm cues (e.g. stimuli from damaged skin) from both wild‐caught and captive‐reared darters, indicating that the diet in captivity did not inhibit the production of alarm cues. Captive‐reared individuals did not change their level of activity when exposed to alarm cues; however, their significantly lower baseline activity (movement and prey consumption) makes it unclear as to whether they actually failed to recognize risk. Regardless, captive‐reared darters showed little motivation to feed when food became available (i.e. they made few movements to obtain food) and appeared impervious to chemical cues indicating risk. Exposing captive‐reared individuals to both semi‐natural foraging opportunities and predator‐recognition training before their release is recommended.